Tax Havens and Their Impact on National Tax Legislation (Lex Scientia Law Review, 2025)
The “offshore economy” constantly dwells in the spotlight of the world community. That creates a number of challenges for the sphere of legislative regulation and assumes the necessity of the implementation of unified international rules into national regulation. This work answers the question of how tax havens affect the tax legislation of individual national legal systems. The study shows the directions and prospects for combating tax evasion through the use of tax havens and concealment of income in offshore corporations. Using political and legal analysis method the paper examines changes in legislative regulation related to tax law under the influence of the offshore zones development and current political and legal responses to the existing challenges associated with tax evasion via tax havens, including in the UK, the EU, and Russia. The research gives grounds to say that at present the OECD action plan BEPS (Base Erosion and Profit Shifting) forms the basis for reforming the relevant legislation not only in the OECD countries, but also outside it. At the same time, in the considered countries, there is a tendency to tighten legislative regulation in terms of business transparency as well as openness of information about the ultimate beneficiary.